The Relationship between the Intensity of Digital Wallet Usage and Students’ Personal Financial Control Ability in Indonesian Universities - Ifoni, Magdalena; Purwantini, Kasih; Reinn, Ishak; Aninditiyah, Galuh (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The development of financial technology in Indonesia, particularly digital wallets, has transformed how university students manage personal finances, facilitating daily transactions but potentially encouraging impulsive spending. This study aims to analyze the relationship between the intensity of digital wallet usage and students’ personal financial control, identify financial behavior factors mediating this relationship, and evaluate differences between heavy and light users. The research employed a quantitative approach with a descriptive correlational design, collecting data through online questionnaires from 150 active university students in Indonesia, complemented by in-depth interviews with three informants to capture subjective perspectives. Data analysis included descriptive statistics, Pearson correlation, and multiple linear regression. The findings indicate that the intensity of digital wallet usage significantly affects students’ financial control; transaction tracking and notification features enhance spending awareness, while aggressive digital promotions may trigger impulsive purchases. These results highlight the importance of digital financial literacy and self-regulation to maximize the benefits of digital wallets. Theoretically, this study expands the literature on digital financial behavior and student self-regulation, while practically, the findings provide implications for universities and digital wallet providers to develop financial literacy programs and application features that promote financial discipline and responsible money management.